Impact of substrate pH and micronutrient fertility rates on Cannabis sativa - Patrick Veazie; Paul Cockson; J. Turner Smith; Brian Schulker; Brian Jackson; Kristin Hicks; Brian Whipker (Agrosystems, Geosciences & Environment)
Abstract Micronutrient accumulation caused by low pH can lead to toxicity and have detrimental impacts on plant growth. In substrates with elevated pH, micronutrients become less available. In the first experiment, industrial hemp (Cannabis sativa L.) growth was less at pH 3.0 and 4.0 than when pH was ≥5.0. Root growth was also observed to be inhibited at low pH levels. Leaf tissue micronutrient concentrations were higher at the lowest pH level, but no toxic accumulation occurred. In experiment 2, root growth had less mass at the lowest pH (3.1) and highest pH level (7.1). In experiment 3, substrates with three target pHs (3.8, 4.8, and 6.5) as well as three micronutrient concentrations (1X, 2X, and 4X) were examined to determine the impact of pH on micronutrient accumulation in two cultivars Cherry Wine (CW) and Sweetened (SW). Foliar micronutrient concentrations were the greatest in plants grown with pH 3.8, and the lowest concentrations occurred in plants grown at pH 6.5. Susceptibility to toxicity from micronutrient accumulation in plant tissue varied by cultivar. SW plants grown at pH 3.8 and 4X micronutrients resulted in lower leaf micronutrient toxicity symptoms, while CW plants grown under the same conditions did not. These studies suggest that C. sativa does not accumulate micronutrients to toxic levels at low pH when micros are applied within normal growing ranges, but that growth is inhibited at substrate pH < 5.0.